2021
DOI: 10.1158/2159-8290.cd-21-0613
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CD4 T-cell Response to SARS-CoV-2: Rationale for PD-1 Blockade in Patients with Cancer and COVID-19?

Abstract: Cancer is a strong risk factor for severe COVID-19 disease. In this issue of Cancer Discovery, Bilich and colleagues demonstrate impaired preexisting and newly generated CD4 T-cell response to SARS-CoV-2 in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Although nocardial brain abscess is commonly secondary to the primary pulmonary site of infection, we couldn’t identify the primary focus in our patient despite a thorough investigation. We assume that the primary infection was subclinical, overshadowed by the CT feature of COVID-19 pneumonia, and masked by a short course of antibiotics that the patient received during the previous hospitalization ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although nocardial brain abscess is commonly secondary to the primary pulmonary site of infection, we couldn’t identify the primary focus in our patient despite a thorough investigation. We assume that the primary infection was subclinical, overshadowed by the CT feature of COVID-19 pneumonia, and masked by a short course of antibiotics that the patient received during the previous hospitalization ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…revealed the pathogenic roles of CCR4 + and CCR6 + T FH cells in COVID-19 patients ( Fenoglio et al., 2021 ). Moreover, it is necessary to pay additional attentions to COVID-19 patients who also suffer from other diseases associated with T FH cell responses, like HIV-infection, autoimmune diseases and cancers treated with immune checkpoint blockade (ICB) therapies ( Picchianti-Diamanti et al., 2021 ; Riou et al., 2021 ; Salomé and Horowitz, 2021 ).…”
Section: Virus-specific T Fh Cells In Covid-19mentioning
confidence: 99%
“…Preexisting and newly generated CD4+ T-cell responses to SARS-CoV-2 were both impaired in patients with cancer (Salomé and Horowitz, 2021). A multicenter study (Sereno et al, 2021) suggested that prolonged granulocyte-colony stimulating factor (G-CSF) treatment was associated with a worse outcome in cancer patients with neutropenia and COVID-19.…”
Section: Introductionmentioning
confidence: 99%